Formulation and comparison of in vitro release profile of hydrophilic and hydrophobic polymer based Naproxen matrix tablets - Kumar Bishwajit Sutradhar, Tajnin Ahmed, Afia Ferdous, Riaz Uddin (Journal of Applied Pharmaceutical Science)
The study was aimed to investigate the effect of polymer on the release profile of Naproxen from different percentages of HPMC 5cps and Kollidon SR based matrix systems. Different amount of HPMC and Kollidon SR were used to develop matrix builder in the four proposed formulations (F1-F4) for the study of release rate retardant effect at 25% and 35% of total weight of tablet matrix respectively. The tablets were prepared by direct compression method. The granules and tablets were evaluated for their physical properties and they did not show any significant variations and were found to have good physical integrity. The dissolution study of those proposed formulations were carried out in the simulated intestinal medium (pH 7.4) for 8 hours using USP paddle method with 50 rpm at 37±0.5°C. HPMC is hydrophilic and Kollidon SR is hydrophobic in nature. Statistically significant difference were found among the drug release profile from different percent of polymer and the release mechanisms were explored and explained with zero order, Higuchi and Korsmeyer equations. The release of Naproxen from F-1 and F-2 very closely followed Korsmeyer release kinetics where F-3 and F-4 best fitted with Higuchi model. The cumulative percent release of Naproxen was highest in F-2 containing 35% of HPMC. On the basis of results, it was found that the profile of F-1 formulation was the best among the four formulations. Between these two polymers, HPMC showed better percentage of release and Kollidon SR showed better release retardant effect.
Keywords: Naproxen, Direct Compression, Sustained Release, HPMC 5cps, Kollidon SR.